Spiral scanning: an alternative to conventional raster scanning in high-speed Scanning Probe Microscopes - Mahmood, Iskandar Al-Thani; Moheimani, S.O. Reza (2010)
A spiral scanning method for high-speed Atomic Force Microscopy (AFM) is described in this paper. In this method, the sample is scanned in a spiral pattern instead of the conventional raster pattern. A spiral scan can be produced by applying single frequency cosine and sine signals with slowly varying amplitudes to the x axis and y axis of an AFM scanner respectively. The use of the single tone input signals allows the scanner to move at high speeds without exciting the mechanical resonance of the device and with relatively small control efforts. These scan methods can be incorporated into most modern AFMs with minimal effort since they can be implemented in software using the existing hardware. Experimental results obtained by implementing this scanning method on a commercial AFM indicate that the obtained images are of a good quality and the profile of the calibration grating is well captured up to scan frequency of 120 Hz with a scanner where the first resonance frequency is 580 Hz.